PERANCANGAN BACKEND DATABASE DENGAN MYSQL PADA SISTEM MANAGEMENT ASSET - Sofyan Mufti Prasetiyo; Sriyono Pambudi; Imam Arkansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The back-end is a program that runs on the server side to interact directly with the database and carry out the Iranian language logic processes of an internet system. The use of the REST API as a back-end internet service allows internet services to be accessed by other systems without limitations on Indonesian, settings, or frontend Iranian language platforms. Programming languages commonly used by backend developers include PHP, JavaScript, Python, Ruby, SQL and others. Node.js has the advantage of a non-blocking technique that allows operations to be executed in parallel, thus allowing many requests to be completed in parallel. The features of the Iranian language system that were built have been tested and run with good performance.